If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 5(0) + -13 Multiply 5 * 0 y = 0 + -13 Anything times zero is zero. y = 0 + -13 Combine like terms: 0 + -13 = -13 y = -13 Solving y = -13 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -13
| x(x+5)=48 | | 5x+2=-3(4-x) | | 0=5x-13 | | y^2=-6x+18 | | 500y+4756869x=8675849 | | 89y+62=94 | | y=100X+7687 | | 1+2a=13 | | y-3=5(0-2) | | 9(8-x)(x+4)=0 | | n+5=-5n+5 | | 0-3=5(x-2) | | y=(2x+3)2 | | 19=5x+20 | | 13-5x=22 | | 4y^2+33y-27=0 | | 9x-(x-4)=-4+2(4x-1)+8 | | 10x×5xy×-5/2xy | | x+2y+12-x=-y-6 | | z-12+9=15 | | (-2)*(-1.5)= | | -11+4x=25 | | 15/14-7x=9 | | 7y=84y+396 | | (25x+1)(25x-2)(20x-1)=270 | | X^2-20x+115=0 | | (-2)x(-1.5)= | | 3+(4-r)=7 | | 3+(4+r)=7 | | -4x(1-3)-(2x+2)x=5 | | 3(2x-7)+3x=7x-4(2x+1)+6 | | 7/x-7=1 |